Digital Transformation in the Labor Market for Disabled Persons (Case Study: an Industrial Company) - V. A. Lipatov; A. A. Solomakhin; I. I. Nekrylov; K. K. Sirbiladze; A. A. Ivanov (Мир новой экономики, 2025)
The impact of digital transformation of industrial enterprises on the labor prospects of people with disabilities is examined by this publication. Distance or hybrid employment and education are effective tools for providing this category of population with highly paid and prestigious jobs in industrial enterprises. Innovative digital technologies, products, resources, and services make it easier for enterprises to adapt workplaces to the unique needs of people with disabilities, which, in turn, contribute to successful economic inclusion. The authors explore microeconomic incentives for enterprises and their impact on corporate HR policy in the context of integrating such workers into the field of employment. Modern industrial enterprises cannot be fully competitive without considering the principles of business social responsibility and an inclusive corporate culture. Microeconomic methods are the main ones to evaluate the effectiveness of labor integration programs in the context of digital transformations. Such approach makes it possible to consider the interests of all stakeholders: employers, employees, and the state, as well as to analyze in detail the possibilities of increasing employment and reducing the unemployment rate of people with disabilities.